Recent advances in PLGA micro/nanoparticle delivery systems as novel therapeutic approach for drug-resistant tuberculosis - Shao, Liqun; Shen, Shu; Liu, Huan (Frontiers in Bioengineering and Biotechnology, 2022)
Tuberculosis is a severe infectious disease caused by Mycobacterium tuberculosis and is a significant public health concern globally. The World Health Organization (WHO) recommends a combination regimen of several drugs, such as rifampicin (RIF), isoniazid (INH), pyrazinamide (PZA), and ethambutol (ETB), to treat tuberculosis. However, these drugs have low plasma concentrations after oral administration and require multiple high doses, which may lead to the occurrence and development of drug-resistant tuberculosis. Micro/Nanotechnology drug delivery systems have considerable potential in treating drug-resistant tuberculosis, allowing the sustained release of the drug and delivery of the drug to a specific target. These properties of the system could improve drug bioavailability, reduce the dose and frequency of administration, and may solve the problem of non-adherence to the prescribed therapy. This study systematically reviewed the recent advances in PLGA micro/nanoparticle delivery systems as a novel therapeutic approach for drug-resistant tuberculosis.